Psoas Hydatid Cyst in Children: A Rare Localization about a Case - Amine El Khassoui (Hindawi Limited, 2021)
Introduction. The development of hydatid cysts in the muscle is rare, and it is even rarer in children. We report the case of a 9-year-old child treated in pediatric orthopedics department at the University Hospital of Marrakech for a hydatid cyst psoas muscle revealed by lameness. Result. The child was consulted for painless and afebrile lameness of the left hip evolving since 3 months. The clinical examination finds a mass of the left flank. Investigations based on the abdominal ultrasound in first intention showed a hydatid cyst depending on the left psoas muscle. Pelvic CT and abdominal MRI were able to confirm the diagnosis and allowed a better study of the cyst neighboring elements. The drainage of the cyst followed by pericystectomy after evacuation of the vesicles contained in the cyst was done as radical treatment. Conclusion. The hydatid cyst of the psoas is a rare entity in the child requiring a good radiological study of the cyst as well as its neighboring elements to propose the most adapted surgery.